Overview of Health Technology Assessment in Hospital settings in the region of the Americas and the Caribbean (Research, Society and Development, 2024)
Objective: This research aims to analyze the practice of hospital-based Healthcare Technology Assessment in Latin America and the Caribbean, focusing on the challenges faced in hospital units. Method: Survey data was obtained from a questionnaire distributed to members of the Brazilian Health Technology Assessment in the region, which inquired about resources, barriers, and training demands, and was analyzed descriptively to provide an overview of the current state of technology assessment at the hospital level in the region. Results: The respondents, representing 64 hospital units from eight countries, reported the following main barriers: a shortage of qualified human resources, high turnover, lack of financial support, an insufficient culture of technology assessment, and the need for continuous training. Conclusion: The findings of this study indicate that they meet significant challenges facing the implementation of hospital-based health technology assessment in the Latin American and Caribbean regions.